If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -15 = -99 Reorder the terms: -15 + 7x = -99 Solving -15 + 7x = -99 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + 7x = -99 + 15 Combine like terms: -15 + 15 = 0 0 + 7x = -99 + 15 7x = -99 + 15 Combine like terms: -99 + 15 = -84 7x = -84 Divide each side by '7'. x = -12 Simplifying x = -12
| -9x-10=4x+16 | | 10/22-2/9= | | 9x+12=26 | | 3.75-.25n+n=13L | | 1x-(-4/5)=-2/3 | | 2x-4(2x-7)=10 | | 16x-(9x-7)=21 | | -5+(7k+3)= | | (8s-6)-(2s+22)=4s-28 | | -5y-4x=15 | | X=2y+164 | | 2(x+7)=-x+4 | | -5+8(x-2)=15x+4-7x | | 2/3(x-4)=1/3(2x/6) | | 2q+(-3)(1-q)=-2q+2(1-q) | | 9x^3-4x^2+x=0 | | 0=-2x-x^2 | | 2x-10/x=1 | | b=80+(25+6) | | 8s-6-2s+22=4s-28 | | 8m+9=8m | | 8z+14=54 | | X-5+2x=-42 | | 4(x+2)+x=10 | | 52+36+17+41+18+29+28+32= | | 4=12x+6y | | 2q+(-3)(1-q)=-3q+2(1-q) | | 112/-7 | | 25=3x+12 | | 1x-1y=6 | | 4(3y-1)=2(2y+3) | | 2.2r-3.8=5.8 |